The drivers of bank credit flow to Agro-processing SMEs in Tanzania: the supply side perspectives - Justus, Gratian Mwemezi (2023)

(untitled)
he study aimed to determine how lending costs, information asymmetry, institutional lending structures, bank credit transparency, and bank financial technology (FinTech) influence the flow of bank credit to Tanzanian agro-processing SMEs. Tanzania promotes agro-processing SMEs to help the country transition from an agricultural to a semi-industrial economy. However, some processing firms are collapsing, while others are not developing as quickly as they should be due to undercapitalization caused by a lack of funding, primarily from banks. By investigating the supply-side perspectives, this study developed a conceptual framework based on financial intermediation theory to better explain the drivers of bank credit flow to agro-processing SMEs. The self-administered questionnaires were collected for statistical analysis utilizing partial least square structural equation modelling in this cross-section quantitative investigation. Three hundred seventy-seven bank branches in five administrative regions in Tanzania were approached by a multistage sampling technique to collect valid responses from lending officers participating in SMEs loans. The empirical findings revealed that information asymmetry and credit risk management significantly negatively influenced bank credit flow compared to lending costs. FinTech and institutional lending structure had a significant positive impact on bank credit flow. Furthermore, the findings demonstrate that FinTech reduces the negative effects of information asymmetry and credit risk management when used as a moderator, allowing Ap-SMEs to obtain more loans. Interestingly, the findings demonstrate that bank credit transparency mediates the relationship between credit risk management and credit flow to Ap-SMEs. This research adds to the body of knowledge about the bank funding of SMEs. Policymakers and practitioners can use the findings of this study to improve credit transparency and financial technology (FinTech) in lending activities to fulfil the nation's goal of creating a semi-industrial economy through agro-processing SMEs.